The Roles of Islands in Áns saga bogsveigis - Martina Ceolin (Cambridge Scholars Publishing, 2017)
References to islands are innumerable in Old Norse-Icelandic literature, especially in sagas including descriptions of travel and communication between Iceland, Scandinavia and the British Isles. In these texts island representation has a pragmatic facet, for example when islands consist in sites along the characters' travel routes. At times, the sources also reveal the symbolic potential of the island setting, when islands host extraordinary events, for instance. Occasionally, the metaphoric quality of islands is also exploited, which is often connected to notions and perceptions of insularity as they are communicated in the texts. For example, Iceland itself is described as both a country and an island in the sources, which allows for interesting parallels to be drawn. The various roles islands play in the sagas will be explored by examining Áns saga bogsveigis, a late medieval fornaldarsaga that shares some characteristics with the genre of the Íslendingasögur. The ways in which islands function in this saga concern both the practical and the more symbolic aspects of island communication, but also the figurative one. An analysis of the most significant island of the story, Hrafnista, will exemplify this, while leading to its interpretation as an allegory of Icelandic sentiments, contemporary to the people involved in the composition and transmission of the saga, vis-à-vis Norwegian and Danish rulership.